2023
DOI: 10.3390/plants12173082
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Adverse Effects of Drought Stress on Growth and Nitrogen Metabolism in Mungbean (Vigna radiata) by Sulphur and Nitric Oxide Involves Up-Regulation of Antioxidant and Osmolyte Metabolism and Gene Expression

Huida Lian,
Cheng Qin,
Jie Shen
et al.

Abstract: The influence of drought induced by polyethylene glycol (PEG) and the alleviatory effect of nitric oxide (50 µM) and sulphur (S, 1 mM K2SO4) were studied in Vigna radiata. Drought stress reduced plant height, dry weight, total chlorophylls, carotenoids and the content of nitrogen, phosphorous, potassium and sulphur. The foliar applications of NO and sulphur each individually alleviated the decline, with a greater alleviation observed in seedlings treated with both NO and sulphur. The reduction in intermediates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…This stress adversely affects yield components such as pod and seed numbers, along with individual seed weight 10 . Furthermore, it lowers plant height, dry weight, chlorophyll content, and essential nutrient levels like nitrogen (N), phosphorus (P), potassium (K), and sulfur (S) 11 . Drought also disrupts mineral uptake and N fixation in legumes 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This stress adversely affects yield components such as pod and seed numbers, along with individual seed weight 10 . Furthermore, it lowers plant height, dry weight, chlorophyll content, and essential nutrient levels like nitrogen (N), phosphorus (P), potassium (K), and sulfur (S) 11 . Drought also disrupts mineral uptake and N fixation in legumes 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [21] suggested that PEG or NaCl can enhance the enzyme activity in the plumules and radicles of alfalfa. Phenolics also play a key role in the plant's defense against ROS-induced damage by eliminating free radicals [22,23]. Drought stress also influences the formation of secondary metabolites, including phenols and flavonoids which enhance plant defense mechanisms [24][25][26].…”
Section: Introductionmentioning
confidence: 99%